The Effectiveness of Yoga on Reducing Women's Anxiety - Horrieh Abbasmofrad (Journal of Modern Psychology, 2023)
The purpose of this study was to investigate the effect of Yoga on women's anxiety. This research was quasi-experimental. The statistical population of the research included women who visited Yoga clubs in Rasht city in 2021. For this purpose, 30 women who had a high score according to the Beck Anxiety Questionnaire (BAI) were selected as a purposive sampling and divided into two experimental (15 people) and control (15 people) groups. Then, Yoga exercises were performed for 8 ninety-minute sessions for the participants of the experimental group, and the control group did not receive any exercises during this period. Then the said questionnaire was again implemented on both groups. The data were analyzed using covariance analysis and SPSS27 software. The results showed that Yoga exercise was effective in reducing women's anxiety (p < 0.05). Therefore, it can be concluded that counselors, psychologists and psychiatrists can use Yoga exercises to reduce women's anxiety.